21st century design : new design icons from mass market to avant-garde - Fairs, Marcus (London : Carlton, 2006)
A fully up-to-date comprehensive survey of the cutting-edge design landscape, guiding the reader through the often bewildering array of contemporary movements, styles and trends and identifying the most important designers working in the world today.
Architecture -- Interiors -- Furniture -- Lighting -- Homeware -- Products -- Clothing and accessories -- Visual communication -- Urban and landscape.
Includes bibliographical references and index.
Keywords: Design -- History -- 21st century